Strategi Lembaga Pendidikan Islam Dalam Menjawab Tantangan Pendidikan Kontemporer - Irawan, M. Nur Lukman; Yasir, Ahmad; Anita, Anita; Hasan, Shohib (Jurnal Pendidikan dan Konseling (JPDK), 2022)
Every person has the right to an education, and that education should be designed to help them realize their full potential as a human being. This study employs a literature research strategy to investigate the issue of Islamic education, which is plagued by a wide range of national problems that disproportionately affect today's youth. These include, but are not limited to, multidimensional crises and contemporary education issues; shifts in emphasis away from teachers and toward students; curriculum problems; and teacher and educational staff turnover and low overall quality. Education policy has been moving in this direction by: (1) allowing schools more autonomy in setting their own rules in light of their unique contexts, Community empowerment to play an active role in providing support and supervision in the world of education; (2) decentralization of education allowing freedom to determine policies based on conditions of Islamic educational institutions; (3) responsible education governed by transparency; (4) relevance of education to the needs and conditions of society; and (5) decentralization of education allowing freedom to determine policies based on conditions of Islamic educational institutions. Substantive, bottom-up, deregulatory, and collaborative approaches are among the options presented.